Result of Endoscopic Third Ventriculostomy for Hydrocephalus Caused by Cerebral Aqueductal Stenosis in Infant Patients - Chowdhury, Forhad H.; Haque, Mohammod R.; Kawsar, Khandkar A.; Sarker, Mainul H.; Haque, Abdul Fazal Mohammod M. (Indian Journal of Neurosurgery, 2017)
Background Endoscopic third ventriculostomy (ETV) is one of the important management options for hydrocephalus, especially obstructive hydrocephalus. The result of ETV in different age and etiology is quite variable according to the different authors. The study was carried out to assess the success rate of ETV as a treatment for this type of hydrocephalus in infant age group.Material and Methods The study was done prospectively on infants (age ≤ 12 months) admitted in the period from January 2009 to June 2013 suffering from obstructive hydrocephalus due to cerebral aqueductal stenosis (CAS). After making the diagnosis, we counseled the patient party about the probability of high failure rate of ETV in this age group and probable necessity of a second operation. With the informed consent, we performed ETV in these cases and followed up regularly in postoperative period. Control neuroimaging studies were done whenever needed (suspected failure of ETV and suspected stomal block).Results Total 17 infants were studied. Average follow-up was 18.7 months. Twelve infants were between the age group of six and under six months while five were above six months to one year old. Fourteen (82.35%) out of 17 patients showed overall clinical improvement. Clinical improvement was seen in two (66.6%) infants aged 2 months or younger, three (75%) aged 2+ to 3 months, five (100%) aged 3+ to 6 months, and four (80%) aged 6+ months to 1 year. Two patients had bleeding during surgery. Three developed CSF leak through the burr hole. In one case (the patient's age was 2 months), the stoma was found blocked, and hydrocephalus returned 9 weeks after ETV. In two patients, in whom VP shunt was needed, “failed ETV” was obvious in early postoperative period. In this series, average ETV success score (ETVSS) was 52.35 (range: 40–70) and overall success rate was 82.35%. This indicates that ETVSS does not correlate with the outcome of ETV in infants with CAS.Conclusion Outcome of ETV for hydrocephalus from CAS in infant is quite good and ETVSS does not correlate with the outcome.
Keywords: endoscopic third ventriculostomy; obstructive hydrocephalus; cerebral aqueductal stenosis; ETV success score; results